Meningkatkan Kemampuan Mengenal Angka 1 Sampai 5 Melalui Media Power Point bagi Anak Down Syndrom (Single Subject Research di Kelas D6/C SLB Luki Padang) - Mega Fitri Yeni; Fatmawati Fatmawati; Markis Yunus (Universitas Negeri Padang, 2013)
This research is motivated by the problems faced by children with Down syndrome in recognizing numbers. The approach used in this study is the experimental approach in the form of single-subject research (single-subject study), using the A-B design and data analysis techniques using visual analysis chart. Thus the hypothesis can be accepted. It means power point media effectively to improve the ability to know the rate for Down syndrome child in SLB Luki Padang. It can be concluded that media power point effectively to improve the ability to know the numbers 1 through 5 on Down syndrome.